118 Developing effective leaders for the integrating care agenda. (3rd November 2019) - Brown, Charlie
Abstract : The Staff College: Leadership in Healthcare (Staff College) is a national charity dedicated to developing leaders and helping them to deliver better outcomes. We design and deliver behavioural based programmes for individuals, teams and Boards within primary, secondary care and the integrated care agenda. Over the last two years we have piloted a variety of approaches to support the development of effective leaders, working to integrate care in their local areas through: Developing the capacity of individual leaders to lead change within the STP through the delivery of a 3–day Senior Clinical Leadership Development Programme. Working with leadership groups to optimise their ability to work together in an atmosphere of trust and mutual respect through the delivery of: STP Board Development Programme STP Work–Stream: Leadership Group Development STP Work–Stream: Development of a Work–Stream Leadership Group Integrating Services Team: Team Development Programme. We'll be presenting the impact these approaches have had for individual leaders and their systems' ability to improve the care of patients at the Leaders in Healthcare Conference 2019, along with the conditions that can make for successful development, and the challenges that can undermine it.